Assessment of sustainable road transport in Lithuania - Renata Činčikaitė (Business: Theory and Practice)
Road transport plays an important role in our lives. In Lithuania, passenger road transport accounted for more than 47% in 2022, and freight road transport more than 87% of the transport sector. Up to 15% of the Lithuanian population works in this sector (in 2020). However, road transport is one of the most polluting. In 2021, it represented 72% of all greenhouse gas emissions from EU domestic and international transport. In order to solve this problem, the EU plans to ban the sale of vehicles with internal combustion engines by 2035. So, the question arises: what challenges will the country’s transport sector face, what measures/innovations will it adopt to reduce greenhouse gas emissions? To answer this question, the article analyzes the road transport sector and identifies measures to improve the sustainability of the sector, increase turnover, and observes the impact of those measures on road transport turnover. The purpose of the research is to determine the factors affecting the circulation of passengers and cargo by road transport based on scientific literature and to empirically verify their influence on the sustainability of the country. In order to achieve the set goal, the analysis is carried out in two blocks: the study of the turnover of road transport cargo and the study of the turnover of road transport passengers. The following methods are used for the research: correlation regression analysis, forecasting. The research results are important for policy makers and practitioners in the context of sustainable transport development.